Enhancing water use efficiency in rainfed Indian-mustard (Brassica juncea L.): Enhancing water use efficiency in rainfed Indian-mustard (Brassica juncea L.) - RAJVIR SINGH,; D K SINGH,; MAHAK SINGH,; H G PRAKASH, (Journal of Oilseeds Research, 2020)
Mustard is the second most important edible oilseed crop of India. It accounts for more than 25 per cent of thetotal oilseed products in the country. A field experiment of Indian mustard was conducted during rabi 2018-19 atOilseed Research Farm, Kalyanpur, Kanpur (U.P.) using different doses of hydrogel and salicylic acid @ 2.5 and5.0 kg and 100 ppm, 200 ppm/ha respectively, using in Indian mustard variety Varuna. The results indicated that the doses of 5.00 kg/ha hydrogel and 200 ppm salicylic acid spray at flowering stage and siliqua formation stage was better. It gave more than 19.98 per cent higher grain yield in comparison to control.